A novel 2-step Titan MPS microwave-assisted synthesis of coconut waste-derived graphene oxide nanocomposites & their photocatalytic evaluation - Balqis, Nuralmeera; Jan, Badrul Mohamed; Metselaar, Hendrik Simon Cornelis; Wahid, Mohd Haniff; Ikram, Rabia (Elsevier B.V., 2026)
This study introduces a novel, sustainable, and eco-friendly 2-step microwave-assisted synthesis of coconut shell waste-derived graphene oxide (GO). Notably, this is the first report of GO synthesis from coconut waste utilizing the Titan microwave preparation system (MPS). In the first step, three samples were carbonized at 200 °C for 1 h using microwave heating. The first sample consisted of 100 g of coconut shell powder mixed with 60 ml of distilled water (DW), the second involved 5 g of coconut powder combined with 8 ml of nitric acid (HNO3), 1 ml of hydrochloric acid (HCl), and 1 ml of hydrofluoric acid (HF), while the third sample used 5 g of coconut powder with 6 ml of HNO3, 0.5 ml of HCl, and 0.5 ml of HF. In the second step, all samples were oxidized using 6 g of potassium permanganate (KMnO4) and then stabilized with 15 mL of hydrogen peroxide (H2O2). The successful synthesis of GO was characterized through various techniques, including Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), and Energy Dispersive X-ray (EDX) analysis. The microwave-assisted method significantly improved the GO yield up to 79%, compared to approximately 20% using conventional methods. Furthermore, TiO2/GO, ZnO/GO, and ZrO2/GO nanocomposites were fabricated using various ratios for photocatalytic degradation. Among all, ZnO/GO (80:20) nanocomposite showed the highest efficiency under visible light irradiation. The results underscore the potential of coconut waste-derived GO nanocomposites as sustainable and efficient photocatalysts for wastewater treatment & other industrial applications.